Age-Related Hypercholesterolemia and HMG-CoA Reductase Dysregulation: Sex Does Matter (A Gender Perspective). (4th May 2010) - Trapani, Laura; Pallottini, Valentina
Abstract : Although cardiovascular diseases are less prevalent in premenopausal women than in men, their occurrence in women increases at the onset of menopause, and the loss of female sex hormones contributes to the striking increase in cardiovascular morbidity and mortality in postmenopausal women. We present here a description of age-related disruption of lipid homeostasis, which particularly affects 3-hydroxy 3-methylglutaryl Coenzyme A reductase, the key rate-limiting enzyme in the cholesterol biosynthetic pathway. We further discuss the age- and gender-related dysregulation of this enzyme, providing new evidence for the different mechanisms driving dyslipidemia in elderly men and women. In addition, we introduce pharmacological methods of regulating HMGR and maintaining cholesterol homeostasis.